2016
DOI: 10.1007/s10532-016-9761-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition

Abstract: The short-cut nitrification (SCN) performance of an airlift reactor (ALR) was investigated under increasing bicarbonate condition. The sequential increase of bicarbonate from 2.5 to 7.0 g/L accelerated the nitrite accumulation and improved the NAP to 99 %. With the increase of bicarbonate dose to 11 g/L, the ammonium removal efficiency and the ammonium removal rate (ARR) were improved to 95.1 % and 0.57 kg/m(3)/day, respectively. However, the elevation of bicarbonate concentration from 11.0 to 14.0 g/L gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This phenomenon is attributed to the breakage of the HBs and crystalline regions of the fibers when water is frozen, thereby reducing the crystallinity and strength of the cellulose fibers . This observation is consistent with previous findings, which suggested that the lower strength of the HBs between adjacent cellulose chains loosens the cellulose structure and lowers the crystallinity of a material, thereby decreasing its mechanical properties. , …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This phenomenon is attributed to the breakage of the HBs and crystalline regions of the fibers when water is frozen, thereby reducing the crystallinity and strength of the cellulose fibers . This observation is consistent with previous findings, which suggested that the lower strength of the HBs between adjacent cellulose chains loosens the cellulose structure and lowers the crystallinity of a material, thereby decreasing its mechanical properties. , …”
Section: Resultssupporting
confidence: 91%
“…Figure presents the crystallinity of S C , S F , and S D obtained through XRD. The signals at 29, 36, 39, 47.5, and 48.5° are diffraction peaks of the calcite-type CaCO 3 fillers . The peaks at 15.4, 16.6, and 22.5° correspond to the crystalline regions of the cellulose fibers .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…During anaerobic digestion process, high F/I easily lead to VFAs inhibition, which usually effects the variation of methanogenic community structure in the bioreactor [24]. Therefore, the effects of intermediate VFAs produced by the increasing of F/I on the methanogenic community structure were analyzed at the end of each stage used the 16S rRNA high throughput sequencing technique.…”
Section: Effect Of Vfas On the Methanogenic Community Under Differentmentioning
confidence: 99%